The association between intracranial haemorrhage and skull fracture in trauma patients at the Hospital Universiti Sains Malaysia (HUSM) - Sohot, Nurul Qomariah Abu (2016)
Introduction Head injury, as defined by the National Advisory Neurological Diseases and Stroke Council, is a morbid state resulting from gross or subtle structural changes in the scalp, skull, and/or the contents of the skull, which is produced by mechanical forces. Majority of fatalities in trauma cases occurs due to head injury. The most common cause of head injury is motor vehicle accident (MVA). In Malaysia, the incidence of motor vehicle accident is one of the highest in the world with about 22 deaths per 100 000 (Liew et al, 2009). Another common cause of head injury is assault and the pattern of injuries depends upon the type of the weapon. The next important cause of head injury is fall from height. The degree of injuries depends upon the height and side of body which hit the ground. The range of trauma to the head varies from mild closed head injury to open skull injury and evisceration of the brain tissue. The brain is an important structure containing the vital centres of respiration and cardiac activity. It is enclosed and partially mobile within the calvarium. Although the skull is tough and provides excellent protection for the brain, a severe impact can result in its fracture. It may be accompanied by injury to the brain. The brain can be affected directly by damage to the nervous system tissue and bleeding. The blood clots that form under the skull can also compress the underlying brain tissue. without having any skull fractures. However skull fractures may provide information about the location of an impact. Skull fracture has several potentially dangerous sequelae. The most common is when the fracture fragment injures the meningeal artery, resulting in intracranial haemorrhage. A depressed fracture may impinge upon the brain parenchyma and the bone fragments may lacerate or penetrate the brain. Many severe head injuries with skull fractures have variable degrees of intracranial injuries. The intracranial injuries ranging from cerebral concussion, contusion, extradural, subdural, subarachnoid haemorrhage and diffuse axonal injuries. Above all, extradural haemorrhage is a neurosurgical emergency. A prospective study done in Hong Kong involving adolescents (11-15 years old) with skull fracture and intracranial haematoma revealed that, of the 418 admitted patients, only 26 had skull fractures, 13 of these develop intracranial haematoma (Chan et al, 1990). Multivariate analysis showed that skull fracture was the only independent significant risk factor in predicting intracranial haematoma in adolescents. A study done by Macpherson et al, 1990 showed the relationship of intracranial contusion and haematoma with the presence, site and type of skull fracture. Of the 1383 patients with head injury, 850 patients had skull fracture, while 846 patients had intracranial haemorrhage. From their study, 601 (71%) of 850 cases with skull fracture had intracranial haemorrhage and 245 (46%) of 533 cases with no skull fracture had intracranial. The main objective of this study is to find out the association between skull fracture and intracranial haemorrhage in trauma patients and the association between types of skull fracture and types of intracranial haemorrhage.